IMPROVING THE EFFICIENCY OF CUSTOMS CONTROL AS A TOOL FOR REGULATING THE MARKET OF POTENT SUBSTANCES - Ф. Гайиров (Ecominds Press, 2026)
This article analyzes the development trends of tourism services exports in Uzbekistan and their role in the national economy based on statistical data. During the research, the flow of foreign tourists, the volume of tourism services exports, and their share in the structure of services exports were studied. The results of the analysis showed the importance of tourism services exports in increasing foreign exchange earnings, diversifying services exports, and strengthening economic stability. Based on the results obtained, scientific conclusions were developed on the further development of tourism services exports.
Keywords: Tourism services exports, foreign tourists, services exports, foreign exchange earnings, tourism infrastructure, economic stability.